Analisis Tarif Angkutan Umum Travel Berdasarkan Biaya Operasional Kendaraan (BOK) Rute Kota Palangka Raya-Kasongan - Isa Ariayini, Brayen Putra Perdana; Ina Elvina; Devia (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
The increase in fuel prices in the City of Palangka Raya has affected the increase in the fares of public transportation in the City of Palangka Raya, one of which is public transport travel. This study aims to analyze Vehicle Operating Costs (BOK) and public transportation fares traveling the City of Palangka Raya-Kasongan route. The research location is at CV. Putra Borneo Travel and CV. Munir Travel uses a sample vehicle, namely the Toyota Innova. Rates that apply in CV. Putra Borneo Travel and CV. Munir Travel for the City of Palangka Raya-Kasongan route is Rp 100,000,-. Vehicle Operating Costs (BOK) and public transport travel fares were calculated using the 2002 Ministry of Transportation method. This research was conducted for 7 days in February 2023. The calculation results show that the highest total Vehicle Operating Costs (BOK) is CV. Putra Borneo Travel is Rp 7544.77/kend-km and the lowest is Rp 6846.79/kend-km. The highest Total Vehicle Operating Cost (BOK) for CV. Munir Travel is Rp 7624.13/kend-km and the lowest is Rp 7225.30/kend-km. The fare for public transportation travel for the City of Palangka Raya-Kasongan route for CV. Putra Borneo Travel, the highest is Rp 104,333,- and the lowest is Rp 94,681,- while for CV. Munir Travel, the highest was Rp 105,431,- and the lowest was Rp 99,916,-. The recommendation is for travel service providers to evaluate travel rates.